Boosting Trade in Egypt - Mohammed Rachid, Rachid (World Bank, Washington, DC, 2012)
Reforming is not for the faint-hearted. The reform path is unpredictable even when all your stones are well-aligned. Indeed, in many cases nothing the author has planned works according to schedule. To prepare for surprises, either pleasant or unpleasant, the author ask the team what they think can go wrong and tell them to expect it to happen. This approach is important in the author role as minister of trade and industry, part of the new economic reform team appointed in 2004 by President Mubarak. The team was tasked with reviving the Egyptian economy to achieve economic growth levels of 6 percent, provide employment opportunities to the 650,000 new entrants to the job market, and double both the foreign direct investment inflows and total trade, through more integration into the world economy. To add to the pressure, elections were due in 2005 and without any demonstrable change, the new cabinet risked not being in government any more. The need for reform was imperative.